Multi-objective optimization in the vibration characteristics of a hydraulic steering system using a conservative and feasible response surface method. Issue 3 (3rd March 2020) - Song, Chang Yong; Lee, Jongsoo; Choi, Ha Young
ABSTRACT: This article addresses the approximate multi-objective optimum design of an automotive hydraulic steering system based on a multi-body dynamics analysis. The design problem of a hydraulic steering system was formulated to determine the design dimensions of a steering mechanism that is able to estimate the multi-objective Pareto-optimal solutions of weight and vibration frequencies that are subject to the dynamic response constraints of the main steering components. The multi-objective Pareto-optimal solutions were calculated using the non-dominated sorting genetic algorithm-II (NSGA-II) based on various approximate models, and reviewed in terms of exploration performance and constraint feasibility. The multi-objective Pareto-optimal solution characteristics according to the approximate model were reviewed to identify a proper approximate model for the engineering design of a hydraulic steering system. The results of the Pareto solution from the proposed optimization methods could improve the vibration performance as well as the weight reduction of hydraulic steering systems.